A clinical trial protocol to treat massive Africanized honeybee (Apis mellifera) attack with a new apilic antivenom - Barbosa, Alexandre Naime [UNESP] (2017)
Background: Envenomation caused by multiple stings from Africanized honeybees Apis mellifera constitutes a public health problem in the Americas. In 2015, the Brazilian Ministry of Health reported 13,597 accidents (incidence of seven cases per 100,000 inhabitants) with 39 deaths (lethality of 0.25%). The toxins present in the venom, which include melittin and phospholipase A2, cause lesions in diverse organs and systems that may be fatal. As there has been no specific treatment to date, management has been symptomatic and supportive only. Methods: In order to evaluate the safety and neutralizing capacity of a new apilic antivenom, as well as to confirm its lowest effective dose, a clinical protocol was developed to be applied in a multicenter, non-randomized and open phase I/II clinical trial. Twenty participants with more than five stings, aged more than 18 years, of both sexes, who have not previously received the heterologous serum against bee stings, will be included for 24 months. The proposed dose was based on the antivenom neutralizing capacity and the number of stings. Treatment will be administered only in a hospital environment and the participants will be evaluated for a period up to 30 days after discharge for clinical and laboratory follow-up. Results: This protocol, approved by the Brazilian regulatory agencies for ethics (National Commission for Ethics on Research - CONEP) and sanitation (National Health Surveillance Agency - ANVISA), is a guideline constituted by specific, adjuvant, symptomatic and complementary treatments, in addition to basic orientations for conducting a clinical trial involving heterologous sera. Conclusions: This is the first clinical trial protocol designed specifically to evaluate the preliminary efficacy and safety of a new antivenom against stings from the Africanized honeybee Apis mellifera. The results will support future studies to confirm a new treatment for massive bee attack that has a large impact on public health in the Americas.